Direct Synthesis of Polymer Nanotubes by Aqueous Dispersion Polymerization of a Cyclodextrin/Styrene Complex. (30th November 2017) - Chen, Xi; Liu, Lei; Huo, Meng; Zeng, Min; Peng, Liao; Feng, Anchao; Wang, Xiaosong; Yuan, Jinying
Abstract: A one‐step synthesis of nanotubes by RAFT dispersion polymerization of cyclodextrin/styrene (CD/St) complexes directly in water is presented. The resulted amphiphilic PEG‐b‐PS diblock copolymers self‐assemble in situ into nanoparticles with various morphologies. Spheres, worms, lamellae, and nanotubes were controllably obtained. Because of the complexation, the swelling degree of polystyrene (PS) blocks by free St is limited, resulting in limited mobility of PS chains. Consequently, kinetically trapped lamellae and nanotubes were obtained instead of spherical vesicles. During the formation of nanotubes, small vesicles first formed at the ends of the tape‐like lamellae, then grew and fused into nanotubes with a limited chain rearrangement. The introduction of a host–guest interaction based on CDs enables the aqueous dispersion polymerization of water‐immiscible monomers, and produces kinetically trapped nanostructures, which could be a powerful technique for nanomaterials synthesis.